Standard versus extended pneumonectomy for lung cancer: what really matters? - Subotic, Dragan (World J Surg Oncol, 2014)
BACKGROUND: It is still not clear whether an intrapericardial pneumonectomy indicates a more advanced stage of the disease compared to a standard pneumonectomy. METHODS: This was a retrospective study of 164 patients who underwent a pneumonectomy for lung cancer. The first group consisted of 82 patients who had a standard pneumonectomy and the second group was 38 patients who had a intrapericardial pneumonectomy, for both groups in the latest 5-year period. The third group was 44 patients with had a sleeve pneumonectomy in the latest 10-year period. The groups were compared in relation to the overall and stage-related survival, influence of T and N factors, operative morbidity and mortality. The statistics used were Kaplan–Meier, U-test, t-test, χ(2) test. RESULTS: There was no statistically significant difference in stage distribution between standard and intrapericardial pneumonectomies; stages I, II, IIIA and IIIB occurred for 10.9% vs 2.6%, 30.5% vs 26.3%, 46.4% vs 65.8% and 12.2% vs 5.3% of patients, respectively. For patients who had a sleeve pneumonectomy, stage IIIA was significantly more frequent. Although the overall survival (63.5% vs 57.6%) and stage-related 5-year survival were better in the first compared to the second group, especially for stage IIIA (58.6% vs 42.6%), these differences were not statistically significant. There were no significant differences in operative morbidity and mortality between groups 1 and 2, but both were significantly higher in the third group (35.7% and 15.9%). CONCLUSIONS: An intrapericardial pneumonectomy does not always indicate a more advanced stage of the disease. The need for an intrapericardial pneumonectomy, either established preoperatively or during the operation, as a single factor, even for marginal surgical candidates, is not strong enough to reject these patients for surgery.